APH(3’)-Ie, an aminoglycoside-modifying enzyme discovered in a rabbit-derived Citrobacter gillenii isolate - Lin, Naru; Sha, Yuning; Zhang, Guozhi; Song, Chunhan; Zhang, Yuan; Zhao, Jingxuan; Huang, Dawei; Lu, Junwan; Bao, Qiyu; Pan, Wei (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundAminoglycoside-modifying enzymes (AMEs) play an essential role in bacterial resistance to aminoglycoside antimicrobials. With the development of sequencing techniques, more bacterial genomes have been sequenced, which has aided in the discovery of an increasing number of novel resistance mechanisms.MethodsThe bacterial species was identified by 16S rRNA gene homology and average nucleotide identity (ANI) analyses. The minimum inhibitory concentration (MIC) of each antimicrobial was determined by the agar dilution method. The protein was expressed with the pCold I vector in E. coli BL21, and enzyme kinetic parameters were examined. The whole-genome sequence of the bacterium was obtained via the Illumina and PacBio sequencing platforms. Reconstruction of the phylogenetic tree, identification of conserved functional residues, and gene context analysis were performed using the corresponding bioinformatic techniques.ResultsA novel aminoglycoside resistance gene, designated aph(3’)-Ie, which confers resistance to ribostamycin, kanamycin, sisomicin and paromomycin, was identified in the chromosome of the animal bacterium Citrobacter gillenii DW61, which exhibited a multidrug resistance phenotype. APH(3’)-Ie showed the highest amino acid identity of 74.90% with the functionally characterized enzyme APH(3’)-Ia. Enzyme kinetics analysis demonstrated that it had phosphorylation activity toward four aminoglycoside substrates, exhibiting the highest affinity (Km, 4.22 ± 0.88 µM) and the highest catalytic efficiency [kcat/Km, (32.27 ± 8.14) × 104] for ribomycin. Similar to the other APH(3’) proteins, APH(3’)-Ie contained all the conserved functional sites of the APH family. The aph(3’)-Ie homologous genes were present in C. gillenii isolates from different sources, including some of clinical significance.ConclusionIn this work, a novel chromosomal aminoglycoside resistance gene, designated aph(3’)-Ie, conferring resistance to aminoglycoside antimicrobials, was identified in a rabbit isolate C. gillenii DW61. The elucidation of the novel resistance mechanism will aid in the effective treatment of infections caused by pathogens carrying such resistance genes.